2013
DOI: 10.1590/s1415-52732013000300001
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding duration and determinants among Brazilian children under two years of age

Abstract: OBJECTIVE: The present study described the duration and identified the determinants of exclusive breastfeeding. METHODS: The study used data from the Pesquisa Nacional de Demografia e Saúde da Criança e da Mulher 2006 (National Demographic and Health Survey on Women and Children 2006). Data were collected using questionnaires administered by trained professionals and refer to a subsample of 1,704 children aged less than 24 months. The estimated durations of exclusive breastfeeding are presented according to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
11
0
9
Order By: Relevance
“…Alguns fatores apresentaram diferenças no tempo de AMT das crianças estudadas, como a idade materna de 18 a 19 anos e a primiparidade. Esses resultados são similares aos de estudos anteriores, que mostraram maior probabilidade de interrupção do aleitamento materno em mães mais jovens 10,17,21,22 e entre aquelas que estavam parindo o primeiro filho. 4,23 De forma semelhante, a influência da idade materna e da paridade na duração do AME foi constatada em revisão sistemática da literatura.…”
Section: Resultsunclassified
“…Alguns fatores apresentaram diferenças no tempo de AMT das crianças estudadas, como a idade materna de 18 a 19 anos e a primiparidade. Esses resultados são similares aos de estudos anteriores, que mostraram maior probabilidade de interrupção do aleitamento materno em mães mais jovens 10,17,21,22 e entre aquelas que estavam parindo o primeiro filho. 4,23 De forma semelhante, a influência da idade materna e da paridade na duração do AME foi constatada em revisão sistemática da literatura.…”
Section: Resultsunclassified
“…21 A baixa da renda familiar e da escolaridade dos pais influenciam no abandono do AME por um motivo em co mum: o desconhecimento dos benefícios em fazê-lo. 22,29 Quando as mães não são bem orientadas, suas crenças podem desconstruir a possibilidade do aleitamento materno. Acreditar que o bebê tem sede e necessita de tomar água e que os chás trarão alívio para as cólicas do recémnascido são alguns dos relatos maternos constantes, porém, a principal crença é a de que o leite é fraco ou em quantidade insuficiente.…”
Section: Discussionunclassified
“…Por fim, um dos estudos demonstrou que não morar na região sudeste é uma situação de risco para o sucesso do AME. 29 Isso pode estar relacionado com as possibilidades de que nessa região as políticas públicas, que protegem a amamentação sejam garantidas, o grau de escolaridade dos pais seja maior e a renda das famílias seja mais elevada se comparada às demais regiões brasileiras.…”
Section: Discussionunclassified
“…It addition, it would be desirable to create or review food regulations, especially those related to the food marketing, which promotes unhealthy foods and/or exerts a negative effect on the knowledge and eating behaviours of the population . Furthermore, breastfeeding should be encouraged in prenatal visits in primary care units, not just in initiatives such as Baby Friendly Hospitals . Finally, where television is a public concession – such as in Brazil – radio and television broadcasters should be required to dedicate part of their prime time to structured health education.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been an increase in the median duration of exclusive breastfeeding (EB), the most recent national estimate is 60 d, far below the recommendation . A multicentre study conducted in Brazil investigated the patterns of fluid intake by children from 3 to 6 years old and found that the consumption of SSBs provided 156 kcal d −1 , which represents ∼13.5% of the recommended daily energy intake .…”
Section: Introductionmentioning
confidence: 99%